2016
DOI: 10.3171/2016.1.focus15613
|View full text |Cite
|
Sign up to set email alerts
|

Adult sports-related traumatic brain injury in United States trauma centers

Abstract: Neurosurg Focus 40 (4):E4, 2016T raumaTic brain injury (TBI) is an alteration in brain function or other evidence of brain abnormality, resulting from an external force applied to the head. Traumatic brain injury occurs in several settings common to daily life, including recreational activities. 21,25,30 In the United States, more than 2.5 million people seek medical care for TBI annually.13 Underreporting of sports-related injuries, lack of consensus definitions, or limited recognition of milder injuries like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…A recent study found equine-related accidents to be the most important contributor to sports-related traumatic brain injuries in the USA (45.2%). 24 The protective effect of riding helmet was shown multiple times before. 9 11 12 25–27 Bilaniuk et al found a significant lower ISS and incidence of intracranial injury in patients wearing a helmet.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found equine-related accidents to be the most important contributor to sports-related traumatic brain injuries in the USA (45.2%). 24 The protective effect of riding helmet was shown multiple times before. 9 11 12 25–27 Bilaniuk et al found a significant lower ISS and incidence of intracranial injury in patients wearing a helmet.…”
Section: Discussionmentioning
confidence: 99%
“…A previous review determined that the sample size of 100 hospitals can be extrapolated to represent the national patient distribution. 56 Detailed data qualification, selection, cleaning, and standardization algorithms have been previously reported. 45 Because the NSP of the NTDB is a fully deidentified data set without the 18 federal Health Insurance Portability and Accountability Act identifiers, the current study was classified as being exempt from institutional review board review.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a group from UCSF has utilized data from the National Sample Program of the National Trauma Data Bank to describe the incidence of pediatric and adult sports-related traumatic brain injury in US Trauma Centers [ 5 •, 6 •]. They estimated that 18,310 adult and 11,614 pediatric TBIs present to level I or level II trauma centers in the USA each year.…”
Section: Epidemiologymentioning
confidence: 99%
“…In children, the mortality was 0.8 % of sports-related TBI. The authors found that the severity of head and extracranial injuries predicted prolonged hospital and ICU stays, medical complications, failure to discharge home, and death, with age and hypotension being additional predictors for the adult population but not for children [ 5 •, 6 •].…”
Section: Epidemiologymentioning
confidence: 99%